PWE-014 Iron therapy and its effect on cell proliferation in human colorectal carcinoma. (17th June 2017) - Evstatiev, R; Ng, O; Al-Hassi, HO; Keeler, BD; Rowther, FB; Khare, V; Jambrich, M; Acheson, AG; Gasche, C; Brookes, MJ
Abstract : Introduction: Oral iron (but not intravenous iron) promotes intestinal tumourigenesis in animal models [1]. This is the first study to examine the effect of iron therapy on proliferation and apoptosis in human colorectal cancer (CRC) in vivo . Method: 30 patients from the IVICA trial with CRC and pre-operative iron deficiency anaemia were given a minimum of 2 weeks iron therapy (15 oral ferrous sulphate, 15 intravenous ferric carboxymaltose) [2]. Tumour tissue and adjacent normal tissue from surgical resection were collected. Protein markers for proliferation (Ki67, betaćcatenin) and apoptosis or DNA damage (p53, γH2AX) were analysed using immunohistochemistry. c-MYC mRNA was examined using real time PCR. Expression was compared with paired normal tissue and differences between treatment groups analysed. Results: All markers of apoptosis, proliferation and DNA damage were more strongly expressed in tumour tissue compared to normal. Differences between treatment groups were seen in these proteins by immunohistochemistry but did not reach statistical significance. The intravenous group had similar Ki67 (35% oral vs 37% IV, p=0.77) and similar nuclear (16% oral vs 13% IV, p=0.6614) and membranous betaćcatenin (67% oral vs 66% IV, p=0.89). Lower p53 (45% oral vs 24% IV, p=0.09) but similar γH2AX (32% oral vs 31% IV, p=0.91) were seen in the intravenous group. c-MYC mRNA fold-change were significantly higher in tumour cells compared with normal tissue (p<0.0001) and increased in both treatment groups with a smaller fold-change in intravenous 3.2 (1.90%–4.50 95% CI) versus oral 4.7 (4.50%–8.20 95% CI) iron therapy. No differences were seen within an MMR-deficient subgroup. Conclusion: IV iron therapy does not cause significant increases in proliferation or apoptosis in tumours when compared to oral iron. This was despite IV iron being more effective in correcting clinical anaemia in the IVICA trial [2]. A trend towards increased proliferation and more apoptosis with oral iron therapy when compared to intravenous iron therapy is seen with c-MYC and p53. Our future studies will include a larger sample number and will also focus on the effect of intravenous therapy on systemic changes of proliferation and apoptosis markers in human colorectal cancer. References: . Seril DN, et al. Systemic iron supplementation replenishes iron stores without enhancing colon carcinogenesis in murine models of ulcerative colitis: comparison with iron-enriched diet . Dig Dis Sci2005;50(4):696–707. . Keeler BD, et al. Randomised clinical trial of preoperative oral versus intravenous iron in anaemic patients with colorectal cancer . Br J Surg2017;104(3):214–221. Disclosure of Interest: None Declared